COVID-19 vaccine immune response in patients with plasma cell dyscrasia: a systematic review - Unaiza Faizan; Lakshmi G. Nair; Maroun Bou Zerdan; Majid Jaberi-Douraki; Faiz Anwer; Shahzad Raza (SAGE Publishing, 2023)
Background: Patients with plasma cell dyscrasia are at a higher risk of developing a severe Coronavirus-2019 (COVID-19) infection. Here we present a systematic review of clinical studies focusing on the immune response to the COVID-19 vaccination in patients with plasma cell dyscrasia. Objectives: This study aims to evaluate the immune response to COVID-19 vaccines in patients with plasma cell dyscrasia and to utilize the results to improve day-to-day practice. Design: Systematic Review Methods: Online databases (PubMed, CINAHL, Ovid, and Cochrane) were searched following the preferred reporting items for systematic review and meta-analysis (PRISMA) guidelines. Only articles published in the English language were included. Out of 59 studies, nine articles (seven prospective and two retrospective studies) were included in this systematic review. Abstracts, case reports, and case series were excluded. Results: In all nine studies ( N  = 1429), seroconversion post-vaccination was the primary endpoint. Patients with plasma cell disorders had a lower seroconversion rate compared to healthy vaccinated individuals and the overall percentage of seroconversion ranged between 23% and 95.5%. Among patients on active therapy, lower seroconversion rates were seen on an anti-CD38 agent, ranging from 6.5 up to 100%. In addition, a significantly lower percentage was recorded in older patients, especially in those aged equal to or greater than 65 years and those who have been treated with multiple therapies previously. Only one study reported a statistically significant better humoral response rate with the mRNA vaccine compared to ADZ1222/Ad26.Cov.S. Conclusion: Variable seropositive rates are seen in patients with plasma cell dyscrasia. Lower rates are reported in patients on active therapy, anti-CD38 therapy, and elderly patients. Hence, we propose patients with plasma cell dyscrasias should receive periodic boosters to maintain clinically significant levels of antibodies against COVID-19. Registration: PROSPERO ID: CRD42023404989